Zakat Muflis Yang Menjadi Kaya Kembali - Nofiardi, Nofiardi (Alhurriyah, 2013)
This paper is for the person who has obligation to issue zakat, because he has fulfilled the pillar and rule of zakat. However, he post ones the issue of zakat and use it as the capital in trading. In trading, he gets losses that depleted his property so that he becomes bangkrupt (muflis). In this condition, he surely cannot issue a charity since there is no treasue that will be issued anymore. Then, after having effort and get differeril opion about zakat paid by muzakki, whether, he will pay the treasure zakat or he is also obliged to pay the debt of zakat before he goes bankrupt (muflis).